Surgically Treated Cases of Lumbar Spondylolysis and Isthmic Spondylolisthesis: A Multicenter Study. Issue 5 (June 2015) - Hirano, Kenichi; Imagama, Shiro; Matsuyama, Yukihiro; Kawakami, Noriaki; Yukawa, Yasutsugu; Kato, Fumihiko; Hachiya, Yudo; Kanemura, Tokumi; Kamiya, Mitsuhiro; Deguchi, Masao; Ito, Zenya; Wakao, Norimitsu; et al.
Abstract : Study Design: Prospective database study. Objectives: To grasp the characteristics of surgically treated cases with lumbar spondylolysis or isthmic spondylolisthesis. Summary of Background Data: A detailed analysis of surgically treated cases with spondylolysis or isthmic spondylolisthesis has never been reported. An epidemiological study in Japan conducted on 2000 subjects found the incidence of lumbar spondylolysis in the Japanese general population (population-based study) to be 5.9% (males: 7.9%, females: 3.9%). Among 124 vertebrae with spondylolysis, there were 0.8% L2 lesions, 3.2% L3 lesions, 5.6% L4 lesions, and 90.3% L5 lesions, including 5 cases (4.3%) with multiple-level lesions. Methods: We have been registering surgically treated spine cases in our database since 2000. From this database, we prospectively collected cases with lumbar spondylolysis or isthmic spondylolisthesis that were treated surgically between January 2000 and December 2009. We determined the age at surgery, sex, and vertebral level of spondylolysis. Results: Of the 564 spondylolysis patients treated surgically, 66.8% were male and 33.2% were female. The mean age at surgery was 52.5 years (range, 13–84 y). There were 585 vertebrae with spondylolysis including 21 cases (3.7%) with multiple-level lesions. L5 spondylolysis affected 432 vertebrae and was the most common location (73.8%), followed by 125 L4 lesions (21.4%), 24 L3 lesions (4.1%), and 2 L2 lesions (0.7%). Conclusions: The percentage of L4 lesions in our study was significantly higher and of L5 lesions was significantly lower than those lesions' percentages in the population-based study. L4 spondylolysis may be more unstable or cause clinical symptoms more frequently leading to more surgical intervention. The percentage of multiple-level spondylolysis was similar between the 2 studies, suggesting these patients respond relatively well to conservative treatment. The male/female ratio was 2:1 in both studies, indicating that males and females require surgery at a similar frequency.